Vascular epiphytes in the Amazon: main gaps, limitations and perspectives for studies on the subject - Ana Laura da Silva Luz; Antônio Augusto de Souza Costa; Clediane Ribeiro Moreira; Felipe Fajardo Villela Antolin Barberena (Acta Botânica Brasílica, 2023)
Abstract Vascular epiphytes stand out in tropical forests in terms of diversity. However, no comprehensive review of the group in the Amazon region has been performed so far. We carried out a literature review on the scientific knowledge of vascular epiphytes in the Amazon aiming to identify the main gaps, limitations and perspectives for studies on the subject. Searches were conducted in Google Scholar, Scopus and Web of Science using inclusion and exclusion criteria. 291 articles published in the period 1933-2022, mostly the 21st century, were included in the review. Brazil was the most studied country. However, knowledge gaps were found in regions located in the Brazilian arc of deforestation as well as in areas of Bolivia, Guyana, French Guiana and Suriname. There was a predominance of studies related to the floristics, systematics and biogeography of spermatophytes and ferns, focusing on the diversity and taxonomy of certain families (e.g. Orchidaceae). However, we found gaps for more comprehensive research, considering population dynamics, dominance (biomass), guidelines for evaluation of epiphyte and systematization of data for Amazon. We indicate the need of studies focused on ecology, floral and reproductive biology, biochemistry, phytochemistry, anatomy and physiology. Future research should also consider the impacts of current trends in deforestation and climatic changes on the diversity of vascular epiphytes in the Amazon.